Streptococcus thermophilus bacteraemia in a patient with transient bowel ischaemia secondary to polycythaemia - Stephens, Joanna; Turner, David P.J. (Microbiology Society, 2015)
Introduction: The ability of Streptococcus thermophilus to convert lactose into lactic acid has long been utilised by the dairy industry. A seemingly low-pathogenicity organism, there have been no previously published reports linking the consumption of foodstuffs to bacteraemia with this bacterium. Case Presentation: Here we present a case of a regular consumer of Activia yoghurt who developed S. thermophilus bacteraemia probably due to transient bowel ischaemia secondary to polycythaemia. Conclusion: The isolation of this bacterium from blood cultures may indicate underlying large bowel pathology and should not necessarily be dismissed as contamination.